2014
DOI: 10.1016/j.jemermed.2013.08.129
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Frequent Emergency Department Users with Alcohol Use Disorders

Abstract: Background Patients with altered level of consciousness secondary to alcohol use disorders (AUDs) often undergo imaging in the emergency department (ED), although the frequency and yield of this practice over time are unknown. Study Objectives We describe the use of imaging, the associated ionizing radiation exposure, cumulative costs, and identified acute and chronic injuries and abnormalities among frequent users of the ED with AUDs. Methods This is a retrospective case series of individuals identified t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Studies from Western countries on time-critical conditions in OOH services are dominated by time-to-treatment and components-of-delay studies – especially regarding AMI, closely followed by sepsis and stroke [5, 6, 11, 31, 36, 37]. However, some of these earlier studies have also investigated the patient pathway for certain time-critical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from Western countries on time-critical conditions in OOH services are dominated by time-to-treatment and components-of-delay studies – especially regarding AMI, closely followed by sepsis and stroke [5, 6, 11, 31, 36, 37]. However, some of these earlier studies have also investigated the patient pathway for certain time-critical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…45 However, the exceptionally high morbidity and mortality of this population should give us pause. 8,12,37,51,52 Because the success of treatment for addiction is highly correlated with internal motivation, these individuals in their current state of indifference have little chance of recovery. 12,53,54 How, then, do we engage these individuals who, despite repeated presentation to EDs, are in fact not seeking help and are often refusing it?…”
Section: Discussionmentioning
confidence: 99%
“…Further, the large variation in the frequency with which intoxicated individuals receive neuroimaging indicates considerable differences in our approaches. [1][2][3] Our ability to use existing guidelines to aid in decisions about whether or not to image these patients is hindered by limitations in the quality of the history and physical examination due to intoxication. The authors of "Traumatic Intracranial Injury in Intoxicated Patients With Minor Head Trauma" 4 showed that many significant intracranial injuries would be missed by translating exiting clinical guidelines to intoxicated patients, a finding that highlights the need to further research this understudied, commonly encountered, patient population and clinical scenario.…”
mentioning
confidence: 99%
“…Although the radiation exposure associated with a single head CT scan is relatively low, cumulative exposure from repeated CT scans for patients who are frequently brought to the ED for intoxication is of potential significance. 2,3,5 On the other hand, the practice of serial examinations has its own less tangible costs. It requires vigilance to ensure that patients are not simply left unattended, may prolong length of stay, and may place patients at risk of delayed diagnosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation